ACADEMIC ADVISORS’ PERCEPTIONS OF ACADEMIC ADVISING IN PUBLIC UNIVERSITIES OF MALAYSIA - Van, Nguyen Thuy; Said, Hamdan (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
This study explored academic advisors’ perceptions toward academic advising implemented at public universities of Malaysia. Using a qualitative research design with cross-site analysis strategy approach, interviews were conducted with eight academic advisors from four Malaysian public universities. Each interview session was assisted by the interview protocol. The interview was recorded and transcribed verbatim. The qualitative data was analysed in the form of thematic analysis with the assistance of NVivo12. Several themes emerged from the initial analysis. Further analysis using several coding and themes revealed one advanced theme namely the outcomes of academic advising and four sub-themes related to student development: academic development, personal development, social development, and career development. This study found that academic development, personal development and career development were the first, second, and third themes most stated while the subtheme social development was hardly stated by the academic advisors when asked regarding their perceptions towards academic advising. The finding of this study implies that social development of students was not part of academic advising tasks of academic advisors from the perspective of Malaysian public universities.